Quintais socioprodutivos da Ilha de Caratateua, Belém (PA): entre reconfigurações e valorização de identidades - Pinheiro, Ruan Rodrigo de Oliveira (2024)
This article aims to analyze the physical transformations in the configuration of the socio-productive backyards that were part of the "Memory Route" (R.M.) project of the Ecomuseum of the Amazon, on Caratateua Island, Belém, PA, in 2019/2020. This objective is linked to a broad analytical reflection that aims to highlight the socio-economic and cultural importance of socio-productive backyards in Belém. In addition to revealing these spaces as strategic to the resilience of different Amazonian families in the face of contemporary crisis contexts, such as the pandemic. The data on which the analysis was based was constructed through bibliographical research, participant observations and interviews with four local families who have socio-productive backyards and who were involved in the project. Through the research carried out, it was possible to understand that the emergence of the families' inclusion in the R.M. led to transformations in their backyards related to improvements in the physical structures of the space. As a result, the backyards were valued economically and socio-culturally.